Proposal of BSC for private institution of higher education under the customer’s perspective (Revista Brasileira de Contabilidade e Gestão, 2014)
The objective of this paper is to propose indicators for evaluating the performance of Customer Perspective through the methodology of Balanced Scorecard (BSC) for a Private Institution of Higher Education from Brazil. The high competition in the field of private higher education justifies the need for these institutions to have well-defined strategies and agility to track results and make decisions. This article with a qualitative approach, is a bibliographic and documentary research and a case study at a private IHE in the city of Florianópolis, SC. Using the BSC, indicators were identified as “image of the institution in society", "employability index of students" and "student satisfaction" that were also mentioned in the works of authors researched in bibliometric survey, showing similarities in the results achieved. The "price level of educational services" was the only indicator not mentioned in the research studied. The definition of performance indicators for the Customer Perspective highlighted the need to take advantage of strategic opportunities until then ignored by the institution studied.
Keywords: private institution of higher education; customer perspective; balanced scorecard; perfomance evaluation